Membangun Indonesia Emas: Tawaran Ibnu Miskawaih untuk Penguatan Pendidikan Karakter (PPK) - Wahid Tuftazani Rizqi (Journal of Contemporary Islamic Education, 2024)
Strengthening Character Education was launched by the government to build and equip students as Indonesia's golden generation in 2045. Islamic education, as one of the pillars of character formation in society, should play a role in strengthening character education and building a golden Indonesia. This research tries to analyze the thoughts of Islamic figures who pay attention to ethics, morals, and character education. So the results can be a reference for the development and implementation of Islamic education. This research is qualitative and is included in the library research category. Data was collected using documentation techniques and analyzed using descriptive-analytic techniques. The analysis steps are data reduction, data presentation, and conclusion. The results of this research show that several components of education are in Ibnu Miskawaih's thinking as one of the Islamic education thinkers. Starting from the objectives, materials, methods, and educational environment. Ibnu Miskawaih's thoughts, which focus on ethics and morals, have an integration that is strengthened by character education's efforts to build the spirit of Pancasila and the character of students.